2015
DOI: 10.1002/chem.201502118
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition and Visual Detection of G‐Quadruplexes by a Dicarbocyanine Dye

Abstract: The interactions of a dicarbocyanine dye 3,3'-diethylthiadicarbocyanine, DiSC2(5), with DNA G-quadruplexes were studied by means of a combination of various spectroscopic techniques. Aggregation of excess dye as a result of its positive charge is promoted by the presence of the polyanionic quadruplex structure. Specific high-affinity binding to the parallel quadruplex of the MYC promoter sequence involves stacking of DiSC2(5) on the external G-tetrads; the 5'-terminal tetrad is the favored binding site. Signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
4
10
0
1
Order By: Relevance
“…Currently known G‐quadruplex binders are often polycyclic aromatic compounds . The optoelectronic properties of such compounds render them suitable for biosensing and imaging in addition to their potential therapeutic use . Recently, we reported a new class of polyheterocyclic aromatics, that is, 1,3,8,10‐tetraazaperopyrenes (TAPPs) .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Currently known G‐quadruplex binders are often polycyclic aromatic compounds . The optoelectronic properties of such compounds render them suitable for biosensing and imaging in addition to their potential therapeutic use . Recently, we reported a new class of polyheterocyclic aromatics, that is, 1,3,8,10‐tetraazaperopyrenes (TAPPs) .…”
Section: Introductionsupporting
confidence: 89%
“…[22,36,37] The optoelectronic properties of such compounds render them suitable for biosensing and imaging in addition to their potentialt herapeutic use. [33,35,[38][39][40] Recently,w er eported an ew class of polyheterocyclic aromatics, that is,1 ,3,8,10-tetraazaperopyrenes (TAPPs). [41][42][43][44] Besides giving rise to promising results in the field of organic electronics, [45][46][47][48] it was shown that watersoluble derivatives can be employed as fluorescencep robes selectively stainingc ell nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…As shown by the surface model in Figure , furanose sugars at the 3′‐tetrad protrude beyond the plane and may hamper putative stacking interactions with the ligand. The higher affinity of the better accessible 5′‐tetrad is not without precedence and has also been observed for other ligands binding to the c‐MYC quadruplex . In further analogy to these studies, the strongly impacted overhangs may also indicate large conformational readjustments with the possible formation of a ligand‐induced binding cavity.…”
Section: Resultssupporting
confidence: 52%
“…As shown by the surfacem odel in Figure 8, furanose sugars at the 3'-tetrad protrude beyondt he plane and may hamper putative stacking interactions with the ligand.T he highera ffinity of the better accessible 5'-tetrad is not without precedence and has also been observed for other ligands binding to the c-MYC quadruplex. [40,41] In further analogy to these studies, the strongly impacted overhangs may also indicate large conformationalr eadjustments with the possible formation of al igand-induced binding cavity.I ts hould be cautioned, however,t hat large changes in protonc hemical shifts upon ligand bindingd on ot necessarily correlate with thermodynamic associationc onstants and only indicate significant ligand-induced perturbations. Thus, whereas chemical shift footprints are very valuablef or an initial localizationo fb ound ligand,t hey do not provide for the unambiguous identification of high-and lowaffinity binding sites, especially when differences in microscopic association constants are only moderate.…”
Section: Interacting Sites Of L4 and C-mycmentioning
confidence: 75%
“…Besides the detection of double-stranded DNA, there is also growing interest for the detection of noncanonical DNA structures like G-quadruplex DNA (G4-DNA) since they are relevant for biological activities such as gene transcription [ 11 , 12 , 13 , 14 ] or telomerase inhibition [ 15 ]. Consequently, many fluorescent probes have been reported that target DNA with high selectivity and efficiency in vitro and in vivo [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Among the many different classes used for the development of DNA-sensitive fluorescent probes, natural products like sanguinarine, coralyne, or berberine ( 1a ) are particularly well suited as starting points because of their combination of favorable photophysical properties with a high biocompatibility and high affinity toward G4-DNA [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%